Nuevas tecnologías y relaciones laborales: el estado de la cuestión - Sempere Navarro, Antonio V.; San Martin Mazzucconi, Carolina (Revista de Derecho, 2019)
The widespread use of new technologies in the workplace is causing, for years, a series of disputes that are being settled primarily by the courts. This study reflects the responses given by jurisprudence, judicial and scientific doctrine to the conflicts about individual and collective using of computer tools, its control by the employer, as well as technological surveillance operated under his management and the possible infringement of workers’ fundamental rights.